Heritage Stone 8. Formation of Pinolitic Magnesite at Quartz Creek, British Columbia, Canada: Inferences from Preliminary Petrographic, Geochemical and Geochronological Studies - Littlejohn-Regular, Alexandria; Greenough, John D.; Larson, Kyle (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2021)
Rocks in the Late Proterozoic Horsethief Creek Group at Quartz Creek in British Columbia display rare ‘pinolitic’ textures resembling those described in some sparry magnesite deposits elsewhere in the world. Elongated white magnesite crystals up to 30 cm long occur in a contrasting, dark, fine-grained matrix of dolomite, chlorite, organic material, clay minerals and pyrite. The rocks are aesthetically appealing for use in sculpture and as dimension stone. The term ‘pinolite’ is derived from the superficial similarities between these unusual textures and pinecones. Petrographic examination indicates that these textures formed when metasomatic fluids replaced primary sedimentary dolomite with magnesite. Fluids moved along fractures and bedding planes with repeated fracturing yielding magnesite crystals oriented in opposite directions on either side of annealed fractures, and broken magnesite crystals adjacent to later fractures. Magnesite contains dolomite microinclusions and has elevated Ca contents that are consistent with its formation by replacement of dolomite. Low concentrations of Cr, Ni, Co, Ti, Sr, and Ba in magnesite also imply formation in a metasomatic rather than a sedimentary environment. The rare earth element (REE) concentrations in the Quartz Creek magnesite are higher than those in most evaporitic magnesite and REE patterns lack the Ce and Eu anomalies that characterize carbonate rocks from sedimentary environments. Enrichment in light REE relative to heavy REE, and the similarities between dolomite, chlorite, and magnesite REE profiles, imply that metasomatic fluids modified the original sedimentary geochemical signature of the dolostones during formation of the pinolite rocks. A Late Ordovician to Early Silurian U–Pb age (433 ± 12 Ma), for titanite in the black matrix surrounding the sparry magnesite is younger than the local host rocks, and also younger than the Mesoproterozoic to Middle Cambrian stratigraphic ages of the host rocks for nearby magnesite deposits. The ca. 433 Ma titanite overlaps the ages for numerous fault-associated diatremes and volcaniclastic deposits in the area. Possibly the igneous activity furnished heat for, and/or was the source for, metasomatic fluids that produced the pinolite deposits.